32-bit RISC-V상에서의 PIPO 경량 블록암호 최적화 구현 - 엄시우; Eum Si Woo; 장경배; Jang Kyung Bae; 송경주; Song Gyeong Ju; 이민우; Lee Min Woo; 서화정; Seo Hwa Jeong (정보처리학회논문지. KIPS transactions on computer and communication systems 컴퓨터 및 통신 시스템, 2022)
PIPO 경량 블록암호는 ICISC’20에서 발표된 암호이다. 본 논문에서는 32-bit RISC-V 프로세서 상에서 PIPO 경량 블록암호 ECB, CBC, CTR 운용 모드의 단일 블록 최적화 구현과 병렬 최적화 구현을 진행한다. 단일 블록 구현에서는 32-bit 레지스터 상에서 효율적인 8-bit 단위의 Rlayer 함수 구현을 제안한다. 병렬 구현에서는 병렬 구현을 위한 레지스터 내부 정렬을 진행하며, 서로 다른 4개의 블록이 하나의 레지스터 상에서 Rlayer 함수 연산을 진행하기 위한 방법에 대해 설명한다. 또한 CBC 운용모드의 병렬 구현에서는 암호화 과정에 병렬 구현 기법 적용이 어렵기 때문에 복호화 과정에서의 병렬 구현 기법 적용을 제안하며, CTR 운용모드의 병렬 구현에서는 확장된 초기화 벡터를 사용하여 레지스터 내부 정렬 생략 기법을 제안한다. 본 논문에서는 병렬 구현 기법이 여러 블록암호 운용모드에 적용 가능함을 보여준다. 결과적으로 ECB 운용모드에서 키 스케줄 과정을 포함하고 있는 기존 연구 구현의 성능 대비 단일 블록 구현에서는 1.7배, 병렬 구현에서는 1.89배의 성능 향상을 확인하였다. PIPO lightweight block ciphers were announced in ICISC'20. In this paper, a single-block optimization implementation and parallel optimization implementation of PIPO lightweight block cipher ECB, CBC, and CTR operation modes are performed on a 32-bit RISC-V processor. A single block implementation proposes an efficient 8-bit unit of Rlayer function implementation on a 32-bit register. In a parallel implementation, internal alignment of registers for parallel implementation is performed, and a method for four different blocks to perform Rlayer function operations on one register is described. In addition, since it is difficult to apply the parallel implementation technique to the encryption process in the parallel implementation of the CBC operation mode, it is proposed to apply the parallel implementation technique in the decryption process. In parallel implementation of the CTR operation mode, an extended initialization vector is used to propose a register internal alignment omission technique. This paper shows that the parallel implementation technique is applicable to several block cipher operation modes. As a result, it is confirmed that the performance improvement is 1.7 times in a single-block implementation and 1.89 times in a parallel implementation compared to the performance of the existing research implementation that includes the key schedule process in the ECB operation mode.